2017
DOI: 10.1186/s13065-017-0264-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid simultaneous determination of indacaterol maleate and glycopyrronium bromide in inhaler capsules using a validated stability-indicating monolithic LC method

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a major cause of morbidity and mortality worldwide. A combination of indacaterol maleate with glycopyrronium bromide has recently been approved as a once-daily maintenance therapy in patients with COPD. The very low dose (μg level/capsule) renders the analysis of such products challenges. This study reports for the first time about HPLC method for the quality control of such combination and it is a stability indicating at the same time.ResultsA rapid, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…1,3 Indacaterol maleate (IND), 5-[2-[(5,6-Diethyl-2, 3-dihydro-1H-inden-2-yl)amino]-1-hydroxyethyl]-8hydroxyquinolin-2(1H)-one, is a long acting b 2agonist (LABA) that stimulates b 2 -receptors, with increased intracellular cyclic adenosine monophosphate (cAMP) levels. 4 This results in improvement of muscle smoothness surrounding the bronchial tubes. It is a once-daily treatment with approved dose long acting b-adrenoceptor agonist (LABA) that improves health status in people with breathlessness, and exacerbation of patients with COPD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 Indacaterol maleate (IND), 5-[2-[(5,6-Diethyl-2, 3-dihydro-1H-inden-2-yl)amino]-1-hydroxyethyl]-8hydroxyquinolin-2(1H)-one, is a long acting b 2agonist (LABA) that stimulates b 2 -receptors, with increased intracellular cyclic adenosine monophosphate (cAMP) levels. 4 This results in improvement of muscle smoothness surrounding the bronchial tubes. It is a once-daily treatment with approved dose long acting b-adrenoceptor agonist (LABA) that improves health status in people with breathlessness, and exacerbation of patients with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Preceding published reports reveal few spectrophotometric 15,16 and HPLC methods for IND. 4,17 However, none of the above studies reported the characterization of DPs of IND. Hence, the current study focuses on the characterization of IND and its stress degradants by using UPLC/DAD/ESI-QTOF and MS/MS method.…”
Section: Introductionmentioning
confidence: 99%
“…10 Zayed and Belal used the HPLC method for determination of a combination of indacaterol maleate and glycopyrronium bromide using tenoxicam as an internal standard. 11 Hussein et al used a potentiometric method for glycopyrrolate determination; they fabricated and studied three different kinds of ion-selective potentiometric sensors using multiwalled carbon nanotubes, polyaniline nanoparticles, and polyaniline microparticles. 12 The aim of this work is the determination of glycopyrrolate in pharmaceutical preparations using different voltammetric techniques, namely linear sweep voltammetry (LSV), cyclic voltammetry (CV), and differential pulse voltammetry (DPV).…”
Section: Introductionmentioning
confidence: 99%